High temperature creep properties of Mo T.Z.M. alloy - Clifton, T. E.; Cook, P. (College of Aeronautics, 1965)
Introduction This memorandum reports a series of experiments to determine some tensile creep properties of Mo T.Z.M. alloy at elevated temperatures in the range 1200°C to 1800°C, the material being in sheet form. A subsequent memorandum will report some creep properties of W-Th02 alloy.